Outcome of Patients Supported by Large Impella Systems After Re-implantation Due to Continued or Recurrent Need of Temporary Mechanical Circulatory Support - Sugimura, Yukiharu; Bauer, Sebastian; Immohr, Moritz Benjamin; Mehdiani, Arash; Rellecke, Philipp; Westenfeld, Ralf; Aubin, Hug; Boeken, Udo; Lichtenberg, Artur; Akhyari, Payam (Frontiers in Cardiovascular Medicine, 2022)
Despite the growing utilization of a large microaxial pump, i. e., Impella 5.0 or 5.5 (Abiomed Inc., Danvers, MA, USA) (Impella 5+) for patients with cardiogenic shock (CS), adverse events including the necessity of re-implantation have not been well discussed. In all 67 patients, in-hospital mortality was 52.2% (n = 35). Explantation of Impella 5+ was performed in 39 patients (58.2%), 22 of whom (32.8%) recovered under Impella 5+, and ten further patients (14.9%) survived after a successful transition to permanent mechanical circulatory support. Embolic events were considerable complications in each access. They occurred in the right arm after the removal of Impella 5+ via a subclavian artery (SA) (n = 3, 9.1%) or in the form of leg ischemia in patients with Impella 5+ via femoral artery (FA) (n = 2, 33.3%). Re-implantation was necessary for 10 patients (14.9%) due to 1) recurrent CS (n = 3), 2) pump thrombosis (n = 5), or 3) pump dislocation (n = 2), all of which were successfully performed via the same access route. In univariate analysis, FA access was a significant risk factor for Impella dysfunction compared to SA access (FA vs. SA, 42.9% vs. 9.8%, p < 0.05, odds ratio 6.88). No statistical difference of overall mortality was observed in patients with Impella 5+ re-implantation (n = 10) compared to patients with primary Impella 5+ support (n = 57) (80.0% (n = 8/10) vs. 47.4% (n = 27/57), p = 0.09). Our results suggested the acceptable clinical outcome of Impella 5+ despite a 15% re-implantation rate. Our observational data may merit further analysis of anticoagulation strategies, including risk stratification for embolic events.